They are three different terms right ?

2p, p+10 and 3p + 2

ya

Log in to add a comment

They are three different terms right ?

2p, p+10 and 3p + 2

ya

Log in to add a comment

Then,common difference between will be same

p+10-2p=3p+2-(p+10)

10-p=3p+2-p-10

18=3p

6=p

p+10-2p=3p+2-(p+10)

10-p=3p+2-p-10

18=3p

6=p

we know that a2-a1 = a3-a2

so here 3p+2-(p+10) = p+10-2p

3p+2-p-10 = 10-p

2p-8 = 10-p

2p+p = 10+8

3p = 18

therefore, p=6

we can even verify the answer by putting value of p in these terms

Now plz mark it as Brainliest answer plz